LITERATURE IN PRIMARY AS CURRICULAR AXIS: AN INNOVATION FULL OF CHALLENGES - Camacho Prats, Alexandre; Bennasar Marroig, Francisca (Avances en Supervisión Educativa, 2016)
This paper presents an educational practice based on the implementation of a resource designed and produced ad hoc, by fostering passion for literature in the last year of primary education. Thus, we are able to reach many contents settled in the curricula of Spanish Language, Social Sciences, Natural Sciences and Social and Civic Values, established in the Spanish Education Act 8/2013, of December 9, for improvement of educational quality (commonly known as LOMCE). The evidence we have tested suggests that students feel a special motivation not only to the rich literary elements at our disposal, but also enrich their knowledge and social values in other academic and personal settings. At this point, we believe that this way of working the curriculum in a more interactive way is a great motivator for the assimilation of content from different areas and skills development element, as it is also capable of being applied to a greater or lesser extent curricular areas and other educational realities.